2020
DOI: 10.1002/adsc.202000245
|View full text |Cite
|
Sign up to set email alerts
|

Double Carbonylation Reactions: Overview and Recent Advances

Abstract: The compounds like amides, carbamates, oxamates, oxamides, α‐keto amides, diketones, esters, ureas, etc. find extensive applications in pharmaceuticals, agrochemicals and organic synthesis. The classical syntheses of these compounds often involve cumbersome routes involving toxic chemicals. The carbonylation reactions such as aminocarbonylation, alkoxycarbonylation, oxidative carbonylation and double carbonylation deliver as an efficient and attractive alternative to the conventional synthetic routes even at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 151 publications
0
17
0
Order By: Relevance
“…No evidence for the formation of the corresponding dicarbonylation or -ketoamide products arising from aryl iodide 15 was observed. 55 Practically, these aminocarbonylative transformations do not require the handling of gaseous CO or pressurized autoclave reactors, as CO is generated ex situ from bench stable liquid reagents (formic acid, mesyl chloride, and triethylamine) in a conveniently sealed two-chamber reaction vessel (COware ® ). Given the current interest in the pharmacological potential of pyrazolo [3,4-b]pyridine derivatives, this methodology would suitably facilitate the rapid synthesis of diverse structural analogues for biological assessment.…”
Section: Paper Synthesismentioning
confidence: 99%
“…No evidence for the formation of the corresponding dicarbonylation or -ketoamide products arising from aryl iodide 15 was observed. 55 Practically, these aminocarbonylative transformations do not require the handling of gaseous CO or pressurized autoclave reactors, as CO is generated ex situ from bench stable liquid reagents (formic acid, mesyl chloride, and triethylamine) in a conveniently sealed two-chamber reaction vessel (COware ® ). Given the current interest in the pharmacological potential of pyrazolo [3,4-b]pyridine derivatives, this methodology would suitably facilitate the rapid synthesis of diverse structural analogues for biological assessment.…”
Section: Paper Synthesismentioning
confidence: 99%
“…5 Both of the carbonyl groups in α-ketoamide can be introduced by a palladium-catalyzed CO insertion reaction known as double car-bonylation, although competitive aminocarbonylation through monocarbonyl insertion has been much more widely applied. 6 Recent studies have revealed that double carbonylation is preferred over monocarbonylation by selection of catalytic systems (Pd/CTFs, Pd/NPs), 7 a , b additives (CuI), 7 c bases (DBU, DABCO), 7 d , e and using alkylamine as a nucleophile, even under atmospheric pressure of CO. However, this protocol is mainly limited to the formation of aryl α-ketoamides, and tandem carbonylation/aminocarbonylation to access alkyl α-ketoamides is scarcely reported in the literature (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Ozawa and Yamamoto in 1982 [ 30 ], the palladium-catalyzed double-carbonylative amination reaction has emerged as an efficient amidation approach to install the ketoamide moiety, as a captivating privileged unit that has a crucial role in modern medicinal chemistry [ 31 , 32 ]. Despite the elevated carbon monoxide pressure that is usually recommended for the production of 2-ketocarboxamides, Han and coworkers described a palladium-catalyzed ligand-free selective double carbonylation method under atmospheric conditions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%